Zastrupitve s heroinom, kokainom, amfetamini, kanabisom, gamahidroksibutiratomin dietilamidom lizergične kisline - Brvar, Miran (Medicinski razgledi, 2009)
The most common illicit drugs in Slovenia that lead to poisoning requiring medical attention are heroin, cocaine, meth/amphetamines, cannabis, gamma-hydroxybutyrate and lysergic acid diethylamide. Heroin has an inhibitoryactivity and causes loss of consciousness, narrow pupils, and slow and shallow breathing. Cocaine and meth/amphetamines have a stimulaing activity and cause restlessness, convulsions and cardiac arrhythmia, as well as an increase in blood pressure and body temperature. Cocaine may also cause myocardial infarction because it promotes the formation of blood clots and atherosclerosis. People who use cannabis most commonly seek medical attention due to anxiety, tremors, rapid heartbeat and chest tightness. Gamma-hydroxybutyrate most commonly causes a transient loss of consciousness, slow and shallow breathing and slow heart rate. The treatment of intoxication with illicit drugs is symptomatic because an antidote is available only for heroin.
Keywords: Nedovoljene snovi; Street Drugs; Poisoning; Amfetamini; Heroin Dependence; Lizerginska kislina, dietilamid; Heroin, zasvojenost; Cocaine; Amphetamines; Kokain; Lysergic Acid Diethylamide; Natrijev oksibat; Sodium Oxybate; Konoplja; Cannabis; droge; prepovedane droge; zastrupitve